Determinants of women's participation in the labor force in the Arab countries - an econometric study using the Panel Data model during the period (2000-2020) - Alateeg, Fatimah Fahd; Nasrulddin, Vivian Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to shed light on the impact of some determinants of women's participation in the labor force in some Arab countries (Saudi Arabia, Qatar, Egypt, Morocco, and Tunisia), during the period (2000-2020). In order to investigate the relationships, the Panel Data model was described to express the relationship between Women's Participation in the Workforce as a dependent variable, and the independent variables associated, which were chosen based on previous studies and researchers' efforts, represented in: Male Unemployment Rate, Female Population, Fertility Rate, and Female Education Level. By specifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified by the statistical program E-views. As expected, the results showed a positive relationship between the dependent variable, and both: the male unemployment rate and the level of female education. Contrary to what was expected, the study showed that the dependent variable was directly associated with the fertility rate, and inversely with the female population. Finally, the results proved that the fertility rate is the most influential variable on the dependent variable, where changing it by one unit changes Women's Participation by 1.202, in the same direction. The study concluded with some recommendations to work to raise the percentage of Arab women's participation in the labor force, including: Providing an appropriate environment to enhance the economic participation of Arab women, by including training programs aimed at qualifying them in line with the needs of the labor market, and the need to continue to encourage women to continue their work education.
Keywords: Labor force; Gender Gap; Economic Growth; Women's Work